2011
DOI: 10.1007/s11695-011-0565-0
|View full text |Cite
|
Sign up to set email alerts
|

C-peptide Predicts the Remission of Type 2 Diabetes After Bariatric Surgery

Abstract: Baseline C-peptide is commonly elevated in morbidly obese patients with T2DM. There was a marked reduction in C-peptide after a significant weight reduction 1 year after surgery with a T2DM remission rate of 78.0%. Thus, bariatric surgery is recommended for obesity-related T2DM patients with elevated C-peptide.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
40
0
3

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 79 publications
(51 citation statements)
references
References 27 publications
8
40
0
3
Order By: Relevance
“…The present study revealed that C-peptide level was positively associated with diabetes remission after RYGB. This result is consistent with previous studies by Lee [19,29]. It is assumed that the elevated C-peptide levels in morbidly obese diabetic patients implicate well-preserved pancreatic β cell function capable enough to compensate for the increased insulin resistance.…”
Section: Discussionsupporting
confidence: 93%
“…The present study revealed that C-peptide level was positively associated with diabetes remission after RYGB. This result is consistent with previous studies by Lee [19,29]. It is assumed that the elevated C-peptide levels in morbidly obese diabetic patients implicate well-preserved pancreatic β cell function capable enough to compensate for the increased insulin resistance.…”
Section: Discussionsupporting
confidence: 93%
“…Many previous studies demonstrated that preoperative fasting C-peptide levels might be helpful for predicting T2DM outcome after RYGB [15][16][17]. In T2DM, C-peptide levels are above the normal range because of a compensatory increase in insulin production.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, C-peptide levels in T2DM patients may reflect their pancreas preserve and predict the success of surgical treatment of T2DM. 47 Preoperative C-peptide was found to be an important predictor of diabetes remission after metabolic surgery in a recent study. 48 Although insulin level has the same meaning as C-peptide level and is also an important predictor of those who may benefit from bariatric surgery, 49 direct measurement of insulin level may be difficult in a T2DM patient receiving insulin therapy.…”
Section: Discussionmentioning
confidence: 97%